2019
DOI: 10.3390/ijms20071564
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Human Hepatic Intrasinusoidal CD56bright Natural Killer Cells against Hepatocellular Carcinoma Cells

Abstract: Hepatic intrasinusoidal (HI) natural killer (NK) cells from liver perfusate have unique features that are similar to those of liver-resident NK cells. Previously, we have reported that HI CD56bright NK cells effectively degranulate against SNU398 hepatocellular carcinoma (HCC) cells. Thus, the aim of this study was to further investigate the phenotype and function of HI NK cells. We found that HI CD56bright NK cells degranulated much less to Huh7 cells. HI CD56bright NK cells expressed NKG2D, NKp46, TNF-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Many immune cells express TRAIL constitutively or following activation and thereby can be cytotoxic to TRAIL-sensitive tumor cells in vitro and in vivo. This has been reported for neutrophils [13,14,17,42,43], monocytes/macrophages [17,47,52,73], DCs [46,49,77,78,79,81,82,83,86,87,91,98,102,103,104], pDCs [84,85,88,91,93,95,96,105], cNK/ILC1s [134,136,137,163,228,282], i NKT cells [218,219,225,227,229], γδ T cells [231,235], and conventional T cells [186,194,283,284,285,286].…”
Section: Trail/drs In the Tumor Microenvironmentsupporting
confidence: 59%
See 1 more Smart Citation
“…Many immune cells express TRAIL constitutively or following activation and thereby can be cytotoxic to TRAIL-sensitive tumor cells in vitro and in vivo. This has been reported for neutrophils [13,14,17,42,43], monocytes/macrophages [17,47,52,73], DCs [46,49,77,78,79,81,82,83,86,87,91,98,102,103,104], pDCs [84,85,88,91,93,95,96,105], cNK/ILC1s [134,136,137,163,228,282], i NKT cells [218,219,225,227,229], γδ T cells [231,235], and conventional T cells [186,194,283,284,285,286].…”
Section: Trail/drs In the Tumor Microenvironmentsupporting
confidence: 59%
“…In those reports were a subset of blood-derived NK cells stained for surface TRAIL, it was found exclusively on the CD56 bright population [128,132] and large inter-individual variability was noted [132]. In contrast to the blood, most [128,133,134] but not all [135] studies demonstrated surface TRAIL expression on human liver CD56 bright NK cells. A similar expression profile was seen in mice, where only a subset of NK cells in the liver, but not in blood, spleen, or lung, constitutively expressed TRAIL [136,137,138].…”
Section: Expression and Function Of Trail/drs In Immune Cellsmentioning
confidence: 99%
“…The activation of NKG2D receptors can promote the release of multiple active proteins from NK cells, such as perforin and granzymes, and can also induce the expression of tumor necrosis factor (TNF) ligand interferon-gamma (IFN-γ) to induce apoptosis of hepatocarcinoma and is beneficial to clean up the tumor ( Figure 6). An exciting novel research results also had been shown that the NK cells with positive CD56 bright located in human hepatic sinuses had effective cytotoxicity against SNU398 hepatoma cells through multiple signaling pathways (such as high expression in NKG2D, NKp46, TRAIL, FasL, and others), which were very helpful for the immunotherapy of hepatocellular carcinoma [66].…”
Section: Activation Of Nkg2d Promotes the Activity Of Nk Cells Againsmentioning
confidence: 99%
“…When the neutralizing antibodies were injected intraperitoneally to deplete CD8 + T cells or NK cells, the cytotoxicity to hepatocellular carcinoma was significantly weakened. On this basis, Hwang et al [66] further explored the phenotype and function of NK cells in human hepatic sinusoids and their cytotoxicity to hepatocellular carcinoma cells. It was found that NKG2D, NKP46, TNF-related apoptosis-inducing ligand (TRAIL), and Fas ligand (FASL) were highly expressed in hepatic intrasinusoidal (HI) CD56 bright NK cells, which had little degranulation effect on Huh7 cells, but could secrete more IFN-γ to produce strong cytotoxicity on Huh7 cells.…”
Section: Ifn-gamma Secreted By Nk Cells Exerts Anti-hepatocarcinoma Amentioning
confidence: 99%
“…These findings suggest that liver-resident NK cells play versatile roles in liver diseases. Human liver-resident NK cells are CD56 bright Eomes hi Tbet lo Hobit + TIGIT + CD69 + CXCR6 + CD49e -; express higher levels of NKG2D, NKp46, TRAIL, and FasL; and possess cytotoxicity against HCC cells [36] . However, liver-resident NK cells within the HCC tissue down-regulate NKG2D [37] .…”
Section: Nk Cells In Hccmentioning
confidence: 99%